2019
DOI: 10.1111/liv.14243
|View full text |Cite
|
Sign up to set email alerts
|

The medical impact of hepatitis D virus infection in Uzbekistan

Abstract: Background & Aims The hepatitis B virus (HBV) is endemic in Uzbekistan but the medical impact of infection with the HBV‐dependent hepatitis D virus (HDV) is unknown in the Country. An Hepatology Center was recently established at the Institute of Virology in Tashkent, which has set up a database enlisting patients with chronic viral liver disorders from all over Uzbekistan; it provides an observatory on the current scenario of viral hepatitis in the Country. Methods The prevalence of HBV monoinfection, hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
0
14
1
1
Order By: Relevance
“…In other parts of Asia, HDV remains a major medical problem in the South Eastern and Eastern parts of Turkey, where anti‐HDV was detected in 28% and 45% of patients with chronic hepatitis B respectively . HDV endemicity is consistent in Uzbekistan, where 80% of patients with HBsAg‐positive cirrhosis were co‐infected with HDV . The median age of patients with HDV cirrhosis was 39 years old, confirming that HDV is the major cause of advanced liver disease and of juvenile cirrhosis in that country.…”
Section: High Prevalence Regionsmentioning
confidence: 77%
“…In other parts of Asia, HDV remains a major medical problem in the South Eastern and Eastern parts of Turkey, where anti‐HDV was detected in 28% and 45% of patients with chronic hepatitis B respectively . HDV endemicity is consistent in Uzbekistan, where 80% of patients with HBsAg‐positive cirrhosis were co‐infected with HDV . The median age of patients with HDV cirrhosis was 39 years old, confirming that HDV is the major cause of advanced liver disease and of juvenile cirrhosis in that country.…”
Section: High Prevalence Regionsmentioning
confidence: 77%
“…In Asia up to 2015, the highest prevalences of chronic HDV liver disease were reported in Pakistan, Iran, Tajikistan, and Mongolia; [8] [9] (Figure 1) a 2019 study has shown that over 80% of HBsAg cirrhosis cases in Uzbekistan are associated with HDV infection. [10] From partial and scattered information the prevalence in China, India and Indonesia appears to be low.…”
Section: Main Textmentioning
confidence: 99%
“…Fortunately, attention and diagnostic facilities are improving, sometimes with surprising results; in Uzbekistan where hepatitis D was not considered by international health agencies a few years ago, a recent survey has shown that the HDV is a major cause of cirrhosis, largely exceeding the impact of HBV monoinfection. 12 In conclusion, HDV infection is the severest form of chronic viral hepatitis known to men. It leads to rapidly progressive liver disease that often culminates in end-stage liver disease and liver cancer.…”
Section: Italy Turkey Uzbekistanmentioning
confidence: 97%
“…Blood donors 5% (10) 7% (8) 8% a Cirrhotics 51% (11) 61.4% b >80% (12) Note: In each country the prevalence of anti-HD in asymptomatic blood donors was many times lower than in cirrhotics. Recognizing the true prevalence of HDV infection, particularly in patients with significant liver disease, may be even more important now that effective treatments to control the infection are being developed, 21 as well as to enforce prevention programmes and to drive resources and investments from international health organizations and pharmaceutical companies.…”
Section: Italy Turkey Uzbekistanmentioning
confidence: 98%